Front Cover: Identification of New Peptide Biomarkers for Bacterial Bloodstream Infection. Issue 2 (13th March 2020) - Ma, Yating; Wen, Xinyu; Kong, Yi; Chen, Chen; Yang, Ming; He, Shang; Wang, Jianan; Wang, Chengbin
Abstract : A novel method is used to study serum peptides of bacterial bloodstream infection (BSI), and four biomarkers are selected to differentiate the infection group. This method provides a new approach for serum peptide analysis in bacterial BSI, offering a novel diagnostic strategy and relevant diagnostic targets. The cover image depicts the flow chart of the entire experiment. This is reported by Yating Ma, Xinyu Wen, Yi Kong, Chen Chen, Ming Yang, Shang He, Jianan Wang, and Chengbin Wang in article number 1900075 .